School management and leadership: classical and contemporary approaches - Μαυρικάκης Ευάγγελος (Education Sciences, 2018)
Educational management and leadership either as closely related or as distinct fields of study, have been in the center of the scientific attention for more than a century. In this respect, major studies have been undertaken concerning the traits and behavior of leaders, as well as the contingency and situational factors that affect leadership.On the other hand, in the field of educational management classic and contemporary theories still coexist, despite their important differences and disagreements in their methodological and epistemological aspects. The aim of this paper is to identify and highlight not only those differences, but also the similarities of existing approaches within and between those two fields. At the same time, through the overview of the relevant studies, the shift of the fields from close to open system approaches and from one sided positivist thinking of the past to the more complex qualitative and quantitative approaches of the present are presented.